PRODUKSI BIOETANOL DARI SAMPAH DEDAUNAN SEKITAR KAMPUS UNAND DENGAN METODE SSF (SIMULTANEOUS SACHARIFICATION FERMENTATION) - Marniati Salim; Elida Mardiah; Yollanda Atmelwidia (Jurnal Riset Kimia, 2014)
Vol 7 No 2ABSTRACTIn this research, cellulose from waste leaves are conversed into ethanol by SSF technologyusing cellulase from Trichoderma viride strain T1 sk. In saccharification process, cellulasebreaks cellulase polymer into glucose. Simultaneously, the formed glucose is conversed intoethanol by invertase produced by Saccharomyces cerevisiaewhich is grew on YPD medium.Waste leaves are pretreatmented using basic solutions : basic NaOH 1 %, NH4OH 8 %, NaOH 1% + NH4OH 4 % and NaOH 1 % + NH4OH 8 % with ratio of solid mather (sample) : liquid(basic solution) 1:10 (w/v) with volume of basic solution 100 mL. Immersion time is variatedfor 24, 48 and 72 hours on 500C. The result of research shows that the use of NaOH 1% +NH4OH 4% gives the highest glucose concentration 933,75 Î¼g/mL with immersion time for 72hours on 500C. After being pretreatmented, sample of 0,4 g waste leaves produce the highestglucose concentration. Measurement by GC/MS shows ethanol concentration 62,41% onfermentation time 96 hours with volume of ethanol 2,45 mL for 0,4 g sample.Keywords : Waste leaves, Pretreatment, Trichoderma viride strain T1 sk, SSF, Bioethanol